Electrocatalytic detection of noxious antioxidant diphenylamine in fruit samples with support of Cu@nanoporous carbon modified sensor. (April 2022) - Sivakumar, Mani; Muthukutty, Balamurugan; Chen, Tse-Wei; Chen, Shen-Ming; Vivekanandan, Alangadu Kothandan; Chen, Shih-Hsun; Hatshan, Mohammad Rafe; Ali, M. Ajmal; Kumar, Mohanraj
Abstract: Herein, the facile synthesis of copper(II) and benzene-1, 3, 5-tricarboxylate (Cu-BTC) and copper nanoporous carbon (Cu@NPC) for the electrochemical detection of diphenylamine (DPA) was systematically investigated. The Cu-BTC and Cu@NPC materials structural, morphological, and thermal stability were evaluated and confirmed using FE-SEM, HR-TEM, XRD, FT-IR, and TGA. The electrocatalytic behavior of sensor materials was examined by cyclic voltammetry (CV) and differential pulse voltammetry (DPV). It is presumed that the structural stability and synergic effect exhibited in Cu@NPC are favorable for enhanced sensitivity and selectivity towards the detection of DPA. The Cu@NPC exhibited a wide linear range (0.09–396.82 μM) and the lowest limit of detection (5 nM). Furthermore, the real sample analysis of the sensor for the detection of DPA in apples and pears confirms its potential capability in practical application. Graphical abstract: Image 1 Highlights: Facile copper nanoporous carbon (Cu@NPC) was synthesized for the electrochemical detection of diphenylamine (DPA). Cu@NPC shows enhanced sensitivity and selectivity towards the detection of DPA. The Cu@NPC exhibited a wide linear range (0.09–396.82 μM) and the lowest limit of detection (5 nM).